Half sandwich-type osmium, ruthenium, iridium and rhodium complexes with bidentate glycosyl heterocyclic ligands induce cytostasis in platinum-resistant ovarian cancer cells and bacteriostasis in Gram-positive multiresistant bacteria - Kacsir, István; Sipos, Adrienn; Kiss, Tímea; Major, Evelin; Bajusz, Nikolett; Tóth, Emese; Buglyó, Péter; Somsák, László; Kardos, Gábor; Bai, Péter; Bokor, Éva (Frontiers in Chemistry, 2023)
The toxicity of and resistance to platinum complexes as cisplatin, oxaliplatin or carboplatin calls for the replacement of these therapeutic agents in clinical settings. We have previously identified a set of half sandwich-type osmium, ruthenium and iridium-centered half sandwich complexes with bidentate glycosyl heterocyclic ligands exerting specific cytostatic activity on cancer cells but not on non-transformed primary cells. The apolar nature of the complexes, conferred by large, apolar benzoyl protective groups on the hydroxyl groups of the carbohydrate moiety, was the main molecular feature to induce cytostasis. We exchanged the benzoyl protective groups to straight chain alkanoyl groups with varying length (3 to 7 carbon units) that increased the IC50 value as compared to the benzoyl-protected complexes and rendered the complexes toxic. These results suggest a need for aromatic groups in the molecule. The pyridine moiety of the bidentate ligand was exchanged for a quinolone group to enlarge the apolar surface of the molecule. This modification decreased the IC50 value of the complexes. The complexes containing [(η6-p-cymene)Ru(II)], [(η6-p-cymene)Os(II)] or [(η5-Cp*)Ir(III)] were biologically active unlike the complex containing [(η5-Cp*)Rh(III)]. The complexes with cytostatic activity were active on ovarian cancer (A2780, ID8), pancreatic adenocarcinoma (Capan2), sarcoma (Saos) and lymphoma cell lines (L428), but not on primary dermal fibroblasts and their activity was dependent on reactive oxygen species production. Importantly, these complexes were cytostatic on a cisplatin-resistant A2780 ovarian cancer cells with similar IC50 values as on cisplatin-sensitive A2780 cells. In addition, the quinoline-containing Ru and Os complexes and the short chain alkanoyl-modified complexes (C3 and C4) proved to be bacteriostatic in multiresistant Gram-positive Enterococcus and Staphylococcus aureus isolates. Hereby, we identified a set of complexes with submicromolar to low micromolar inhibitory constants against a wide range of cancer cells, including platinum resistant cells and against multiresistant Gram-positive bacteria.